Legislation Related to E-Cigarettes in The Gulf Cooperation Council Countries - Chehab, Mohamad (Asian Pac J Cancer Prev, 2020)
Even though 90% of the world’s population is covered by the World Health Organization’s Framework Convention on Tobacco Control, it is estimated that only one-fifth (21%) and half (49%) of the countries that ratified this convention will achieve the target of reducing tobacco use by 30 % among men and women respectively in 2025. Over the past decade, there has been an increasing trend in the use of electronic cigarettes or e-cigarettes for recreational use as well as smoking cessation. In concurrence with the increasing use of e-cigarettes among smokers of different age groups, nations have developed relevant national regulations on its sale, advertisement, packaging, product regulation, taxation, and surveillance. The countries of the Gulf Cooperation Council (GCC) region have also witnessed several legislations, at varying extent, related to the use of electronic cigarettes. However, the evidence on the use of electronic nicotine delivery systems remains scarce in the GCC region. Thus, further research on this emerging public health issue is warranted to generate the evidence necessary for the formulation of comprehensive tobacco control laws and effective prevention strategies.